2006
DOI: 10.1007/s10560-006-0049-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of an Alcohol Prevention Program with Urban American Indian Youth

Abstract: In comparing alcohol use among American Indian and nonIndian youth, the age at first involvement with alcohol is younger for Indians, the frequency and amount of drinking are greater, and the negative consequences are more common. This article presents the results of an innovative alcohol prevention program for urban Indian youth, blending mainstream prevention approaches with culturally appropriate intervention. A quasi-experimental treatment/non-equivalent control group research design was used to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 34 publications
(36 reference statements)
1
33
0
Order By: Relevance
“…At the 3½-year follow-up point, however, the bicultural skills CSI group reported lower rates of smokeless tobacco, alcohol, and marijuana use compared to the control group. Thus, the findings echo those reported by Moran and Bussey (2007) in that significant effects emerged only some time after the intervention was completed. Significant differences were not reported for cigarette use at any follow-up point and the addition to the community resources dimension did not appear to provide any additional protective influence beyond that provided by the bicultural skills.…”
Section: Inconsistent or Nonsignificant Csi Effectssupporting
confidence: 86%
“…At the 3½-year follow-up point, however, the bicultural skills CSI group reported lower rates of smokeless tobacco, alcohol, and marijuana use compared to the control group. Thus, the findings echo those reported by Moran and Bussey (2007) in that significant effects emerged only some time after the intervention was completed. Significant differences were not reported for cigarette use at any follow-up point and the addition to the community resources dimension did not appear to provide any additional protective influence beyond that provided by the bicultural skills.…”
Section: Inconsistent or Nonsignificant Csi Effectssupporting
confidence: 86%
“…The clients’ reconciliation of mainstream religious beliefs with traditional Native beliefs allows clients to function successfully in two very different worlds. Experts have concluded that when substance abuse intervention programs modify mainstream prevention programs with cultural elements relevant to urban Natives, the experimental groups show greater improvement in substance use measures at posttest and at a 6-month follow-up (Moran & Bussey, 2007). Furthermore, self-identification with both Native and Western cultures has been associated with increased levels of psychological well-being, including higher self-esteem, more internal locus of control, and fewer behavioral problems when compared with those who connected only with one identity or with neither (Moran & Bussey, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Experts have concluded that when substance abuse intervention programs modify mainstream prevention programs with cultural elements relevant to urban Natives, the experimental groups show greater improvement in substance use measures at posttest and at a 6-month follow-up (Moran & Bussey, 2007). Furthermore, self-identification with both Native and Western cultures has been associated with increased levels of psychological well-being, including higher self-esteem, more internal locus of control, and fewer behavioral problems when compared with those who connected only with one identity or with neither (Moran & Bussey, 2007). In the light of the socio-demographic diversity of the clientele, traditional ritual healing activities are often referred to as “pan-Indian,” meaning that they are based on the tribal heritage, language, and subsequent training of the employee(s) who are leading them.…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous youth are more likely than youth in the general population to misuse substances (Gilchrist, Schinke, Trimble, & Cvetkovich, 1987;Moran & Bussey, 2007;Petoskey, Van Stelle, & De Jong, 1998). In regards to 3 The reader is reminded that the concepts of "risk factors", as well as "protective factors", are often noted in the literature, without adequately noting their dimensions (linear, non-linear; rates of development and decay; anchoring or integration, cessation, etc.…”
Section: Historical Trauma Health Disparities and Ongoing Structuramentioning
confidence: 99%